Parents'/caregivers' fears and concerns about their child's epilepsy: A scoping review. - Bernie Carter; Georgia Cook; Lucy Bray; Amber Collingwood; Holly Saron; Alison Rouncefield-Swales (PLoS ONE)
Background Childhood epilepsy is a serious and common neurological condition and can have life-long consequences and its impact can pervade all aspects of family life. Whilst the medical management of seizures is important, much of the day-to-day home management of epilepsy is invisible to people external to the family, including health care professionals, and parents'/caregivers' fears and concerns can go unacknowledged and unaddressed by health care professionals. Objective This objective of this review was to examine parents'/caregivers' fears and concerns regarding their child's epilepsy, the impact of these fears and concerns on family life, the social and emotional well-being of parents/caregivers and any factors which mitigate these fears and concerns. Design Scoping review using a modified version of Arksey and O'Malley's framework. Data sources Relevant studies were identified using key search terms in Scopus, Medline, CINAHL and PsychInfo databases in March 2021 with hand checking of reference lists. Search terms were developed using population (parents/caregivers of children aged ≤ 18 years with epilepsy, families); concept (parents'/caregivers' fears, concerns, anxiety about their child's epilepsy); and context (any setting). A further search was run in April 2022. Other inclusion criteria: English language empirical studies, 2010-2021. Study appraisal methods A minimum of two reviewers independently screened articles and undertook data extraction and decisions were consensually made. Methodological quality appraisal was undertaken using the Mixed Methods Appraisal Tool v2018. A data extraction table was created to chart all studies. The conduct and reporting of this study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidance for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) (S1 Table). There is no published copy of the review protocol. Main findings The search identified a total of 4077 papers (after duplicates were removed) of which 110 were assessed for eligibility. Twenty-four papers published between 2010-2021 were included in the review and each paper was treated as a separate study. The review findings indicate that parents'/caregivers' fears and concerns stem from more than their child's seizures and relate to many wider aspects of family life. These fears and concerns had far-reaching influences on their parenting/caregiving, and on the lifestyle and activities of their child and their family. What was less evident was what parents/caregivers wanted in terms of support or how they thought health professionals could acknowledge and/or allay their fears and concerns. The discussion is framed within the compassion-focused therapy model as a basis for generating new thinking about the impact of these fears and concerns and the need for a new agenda for clinical consultations in childhood epilepsy. Conclusions The review concludes with a proposal that a more compassionate agenda underpins the dialogue between parents/caregivers and clinicians to encompass and mitigate the wider emotional, psychosocial, and societal threats that impact on the parent/caregivers of children with epilepsy.